The STRATEGY FOR ACCELERATING THE ALLEVIATE OF HOME OWNERSHIP BACKLOGING FOR LOW-INCOME COMMUNITIES IN URBAN AREAS IN NORTH SUMATERA - Dumora Jenny Margaretha Siagian; Porman Juanda Marpomari Mahulae; Sahat Christian Simanjuntak (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2021)
This study aims to understand the various problems in efforts to alleviate the housing backlog, as well as to present a strategy to alleviate the problem of housing backlog for low-income households in North Sumatra. This research uses descriptive method with the main approach is a qualitative approach, which is complemented and strengthened by quantitative data. The data collection techniques used were observation (observation), in-depth interviews, Focus Group Discussion (FGD) and literature study. Based on the results of tracing the housing development conditions in North Sumatra and the identification of the problems carried out, using the SWOT matrix strategy analysis, it is concluded that the acceleration strategies that can be carried out by provincial and municipal governments to alleviate housing backlogs for urban low-income families in North Sumatra are: 1) Aggressive strategy (SO). Optimization of Regional Government and Central Government Housing Development Programs, to add new housing for low-income people in urban areas of North Sumatra; 2) Diversification strategy (ST). Fully supports housing development for low-income housing carried out by the central government and developers (provision of unproductive land / land use, sharing of housing development targets with the central government, data collection and mapping of urban MBR, additional space allocation for urban residential areas in RTRW, optimization the implementation of PP 64 2016); 3) Defensive strategy (WO). Forming effective regional PKP partnership institutions (local government, academia, private sector, financial institutions and the community), in an effort to control the population growth rate, increase the empowerment of urban MBR, provide housing development incentives, control the distribution of housing finance for low-income families, and control the flow of urbanization; and 4) Turn around (WT) strategy. Making the issue of the backlog of home ownership for MBR a priority for regional development. Keywords: Home ownership backlog, low income community (MBR), urban